2010
DOI: 10.1016/j.juro.2009.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors of Papillary Renal Cell Carcinoma: Results From a Multi-Institutional Series After Pathological Review

Abstract: In its current form the 2002 UICC TNM staging system is not applicable to papillary renal cell carcinoma. Clinical and radiological followup should be offered at frequent intervals to patients with venous thrombus and/or locally advanced disease. The role of age remains unclear but should not be underestimated in risk stratification after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Either both or at least 1 of these variables has been reported as predictors of outcome in a recently published large series of papillary RCCs [1417]. In addition to the results of our study, the aforementioned series highlight the importance of T stage and Fuhrman grade in defining the prognosis of patients with papillary RCC.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Either both or at least 1 of these variables has been reported as predictors of outcome in a recently published large series of papillary RCCs [1417]. In addition to the results of our study, the aforementioned series highlight the importance of T stage and Fuhrman grade in defining the prognosis of patients with papillary RCC.…”
Section: Discussionsupporting
confidence: 74%
“…In addition to the results of our study, the aforementioned series highlight the importance of T stage and Fuhrman grade in defining the prognosis of patients with papillary RCC. Moreover, variables such as patient’s age, sex, and multifocality were consistently irrelevant for prognosis in ours and other studies [1416]. Finally, another pathologic feature that has gained attention recently as a putative prognosticator of outcome is the subtype of papillary RCC, according to the classification of Delahunt and Eble [18].…”
Section: Discussionmentioning
confidence: 53%
“…pT1a and pT1b; pT2a and pT2b; and pT3a and pT3b), and the classification did not predict RFS and CSS in multivariable analysis once adjusted for the other covariates. Previous studies had addressed the prognostic role of the previous version of the pathological stage of the primary tumour in pRCC series, showing an independent predictive role for 2002 T stage [4,8,10,12,13,20,21]. However, all of the studies clustered localized and locally advanced pRCC into two subgroups (pT1–2 vs pT3–4), again emphasizing the inadequacy of the staging system generated for ccRCC in stratifying the outcome of pRCC.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer‐specific survival (CSS) estimates at 5 years were reported in the range 70–87% for pRCC [4,6–8,10–13], with stage and grade being the most recognized prognostic factors, although several studies provided conflicting results. The prognostic role of tumour subtype is controversial, with some studies supporting it [9,10] and many others refuting it [4,7,8,13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggest that pRCC is associated with a lower risk of renal vein or IVC extension [23] and that patients with pRCC of pT3 or greater at baseline have an unfavourable prognosis [24]. Another study of 2157 patients, including 245 with pRCC and 1912 with cRCC, found that pRCC patients with a venous tumour thrombus experienced significantly lower CSS rates compared to cRCC patients, and also that the presence of a venous tumour thrombus was an independent prognostic factor for pRCC but not for cRCC [11].…”
Section: Discussionmentioning
confidence: 99%